Recovering Turkish narrow clawed crayfish (Astacus leptodactylus) populations carry Aphanomyces astaci - Kokko, H.; Koistinen, L.; Harlioglu, M. M.; Makkonen, J.; Aydin, H.; Jussila, J. (Edp Sciences S A, 2012)
Crayfish stocks collapsed in Turkey in mid 1980's due to crayfish plague epidemics, with up to 25% survival in some cases. The collapsed stocks have then recovered slowly and commercial crayfish fishery was reinitiated gradually within a decade. We examined the prevalence of Aphanomyces astaci DNA in the narrow clawed crayfish (Astacus leptodactylus) collected from two Turkish lakes, Lake iznik and Hirfanli Dam (N = 40 from both sites). The qPCR results, verified by conventional PCR and sequencing, indicated that nearly all sampled crayfish were A. astaci carries with some of them showing gross symptoms of infection, such as tissue erosion and melanisation, while some did not show any visible symptoms. The prevalence of A. astaci DNA was high in both stocks, being on the average 95% in both Lake iznik and Hirfanli Dam. Our results show that these stocks are carries of A. astaci, but capable of forming productive stocks which indicates past and contemporary partial resistance adaptation in the host or virulence evolution in the A. astaci.
Des populations turques d'écrevisses à pattes grêles (Astacus leptodactylus) productives porteuses d'Aphanomyces astaci
Keywords: Aphanomyces astaci; narrow clawed crayfish; Turkey; iznik; Hirfanli